Evaluation of Pedagogical Leadership through the Vanderbilt Assessment of Leadership in Education (VAL-ED) Adaptation to the Context of Higher Education in Spain : A Corresponding Response - FERNANDEZ, CHARISSA MAY (International Journal of Arts, Sciences and Education, 2023)
This correspondence response is sent in response to the study "Evaluation of Pedagogical Leadership through the Vanderbilt Assessment of Leadership in Education (VAL-ED): Adaptation to the Context of Higher Education in Spain." The study carefully considers the opportunities and difficulties that arise when the VAL-ED tool—which was initially created for K–12 education—is modified to fit the particulars of higher education in Spain. The authors' commitment to thorough research is demonstrated by the successful adaptation of VAL-ED, which also makes a substantial contribution to the field of educational leadership in the Spanish setting.